Acute effect of pore-forming Clostridium perfringens ε-toxin on compound action potentials of optic nerve of mouse - Cases, Mercè; Llobet, Artur; Terni, Beatrice; Gómez de Aranda, Inmaculada; Blanch, Marta; Doohan, Briain; Revill, Alexander; Brown, Angus M.; Blasi, Juan; Solsona, Carles (Society for Neuroscience, 2017)
ε-Toxin is a pore forming toxin produced by Clostridium perfringens types B and D. It is synthesized as a less active prototoxin form that becomes fully active upon proteolytic activation. The toxin produces highly lethal enterotoxaemia in ruminants, has the ability to cross the blood–brain barrier (BBB) and specifically binds to myelinated fibers. We discovered that the toxin induced a release of ATP from isolated mice optic nerves, which are composed of myelinated fibers that are extended from the central nervous system. We also investigated the effect of the toxin on compound action potentials (CAPs) in isolated mice optic nerves. When nerves were stimulated at 100 Hz during 200 ms, the decrease of the amplitude and the area of the CAPs was attenuated in the presence of ε-toxin. The computational modelling of myelinated fibers of mouse optic nerve revealed that the experimental results can be mimicked by an increase of the conductance of myelin and agrees with the pore forming activity of the toxin which binds to myelin and could drill it by making pores. The intimate ultrastructure of myelin was not modified during the periods of time investigated. In summary, the acute action of the toxin produces a subtle functional impact on the propagation of the nerve action potential in myelinated fibers of the central nervous system with an eventual desynchronization of the information. These results may agree with the hypothesis that the toxin could be an environmental trigger of multiple sclerosis (MS).